2020
DOI: 10.1136/annrheumdis-2020-eular.2383
|View full text |Cite
|
Sign up to set email alerts
|

Op0010 effectiveness of the Making It Work™ Program at Improving Presenteeism and Work Cessation in Workers With Inflammatory Arthritis – Results of a Randomized Controlled Trial

Abstract: Background:Arthritis often leads to presenteeism (decreased at-work productivity), missed days from work and permanent work disability, leading to reduced quality of life and high costs to individuals and society. Yet, health services addressing the employment needs of people with arthritis are lacking.Objectives:We evaluated the effectiveness of the Making-it-WorkTM(MiW) program, an online self-management program developed to help people with inflammatory arthritis (IA) deal with employment issues.Methods:A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…OT has been associated with improved work outcomes (49). It is important to note that while the 2022 ACR Guideline for Exercise, Rehabilitation, Diet, and Additional Integrative Interventions for Rheumatoid Arthritis reports that there were no studies that supported interventions at work for people with RA, workrelated OT interventions exist but were not included in the guideline because they did not examine only people with RA (50)(51)(52)(53). Although ergonomics assessment and work self-management are effective strategies to reduce work disability, few workers with RA are referred for work interventions.…”
Section: Comprehensive Occupational Therapymentioning
confidence: 99%
“…OT has been associated with improved work outcomes (49). It is important to note that while the 2022 ACR Guideline for Exercise, Rehabilitation, Diet, and Additional Integrative Interventions for Rheumatoid Arthritis reports that there were no studies that supported interventions at work for people with RA, workrelated OT interventions exist but were not included in the guideline because they did not examine only people with RA (50)(51)(52)(53). Although ergonomics assessment and work self-management are effective strategies to reduce work disability, few workers with RA are referred for work interventions.…”
Section: Comprehensive Occupational Therapymentioning
confidence: 99%
“…Although present interventions for reducing work disability have been mainly in person, as a result of the widespread use of online learning and communication platforms, self-management programs have been adapted to e-learning and telehealth delivery methods (Luquini, et al, 2020, Carandang et al, 2022MacIver et al, 2021).…”
Section: Individual Work-based Rehabilitation Interventions Focussing Onmentioning
confidence: 99%
“…However, a more recent study in United Kingdom testing an individual-based vocational rehabilitation programme, achieved significant workrelated improvements, including reduced presenteeism and absenteeism (Hammond et al, 2017). Similarly, a self-management webbased programme in Canada, Making It Work, proved effective in improving presenteeism and preventing short-term work cessation (Luquini et al, 2020). Although both of these interventions resulted in significant improvements in work performance, individuals participating in an Irish study indicated a preference for a group-based intervention which would provide them with an opportunity to meet others with similar conditions (Connolly et al, 2015(Connolly et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%